Oil price drivers, geopolitical uncertainty and oil exporters' currencies - Qaisar Farooq Akram (Norges Bank, 2019)
Empirical relationships between crude oil prices and exchange rates of oil exporting countries tend to vary over time. I use econometric models of the norwegian and canadian nominal exchange rates to investigate whether such time-variation could reflect shifts in the key oil price drivers over time. Results suggest that demand- and supply-driven oil price increases strengthen these currencies to different extents. In contrast, heightened geopolitical uncertainty and associated oil price increases go together with a weakening of oil exporters' currencies. The latter result may explain coincidences of higher oil prices and a weakening of oil exporters' currencies.
hdl:11250/2652837
Keywords: F31; F32; Q41; C22; C51; 330; Exchange rates; commodity currencies; oil prices; uncertainty